Respon Imun Spesifik Larva Ikan Mas (Cyprinus carpio) melalui Imunitas Maternal yang Diberi Vaksin Inaktif Whole Cell Aeromonas salmonicida - Syohibahttul Islamiyah BAHAR; Esti HARPENI; Eko EFFENDI (Biospecies, 2017)
Aeromonas salmonicida are specific bacteria that can cause infections and death to the cultivation of carp (Cyprinus carpio) during larval stage. Death in carp can be prevented by a vaccine, but the vaccine can only be given on the seed over the age of 3 weeks. Maternal vaccination needs to be done to improve the immune system of the larvae by means of inactivated whole cell vaccine A. salmonicida on broodstock ready to spawn. Aims to determine the effectiveness of vaccines on breeders carp to the parent antibody titer test and larvae, as well Survival Rate (SR) and the Relative Percent Survival (RPS) larvae. This research was conducted with a completely randomized design, 4 treatments A (control); B (0.3 ml/kg); C (0.4 ml/kg); D (0.5 ml/kg) and 3 repetitions. The results show that the antibody titer of 0.3 ml dose capable of providing agglutination reaction to pitting 7th (64x dilution) in broodstock, and vaccine doses 0,4ml on broodstock able to give agglutination reaction to the larvae until all 6 wells (32x dilution). A dose of 0.4 ml/kg resulted the highest SR and RPS with 96.11% and 81.25% respectively. Clinical symptoms of redness in control larvae was spread throughout the body whereas on the vaccine treatment was only in certain body parts.Keywords: A. salmonicida, vaccines, maternal immunity, larva, specific immune responÂ